Isogeometric Analysis and Applications 2014 - Jüttler, Bert; Simeon, Bernd (Lecture Notes in Computational Science and Engineering,, 2015)
Isogeometric Analysis is a groundbreaking computational approach that promises the possibility of integrating the finite element  method into conventional spline-based CAD design tools. It thus bridges the gap between numerical analysis and geometry, and moreover it allows to tackle new cutting edge applications at the frontiers of research in science and engineering. This proceedings volume contains a selection of outstanding research papers presented at the second International Workshop on Isogeometric Analysis and Applications, held at Annweiler, Germany, in April 2014.